الخطاب السجالي مفهومه و خصائصه و علاقته بالمعرفة - عبد الكبير, نور الدين (جامعة الوادي - University of Eloued, 2023)
ملخص: تحاول هذه الدراسة أن تطلعنا على أن الخطاب السجالي يبقى خطابا ابستملوجيا، يسعى إلى بناء المعرف أو المشاركة فيها، من خلال قيامه على تقديم بديل إبستيمولوجي يغنى المعرفة أو يغذيها ويرسم مبدأ الاختلاف في الرأي، ويدافع عن قيمة الإبداع الذي يناقض التبعية والتحجر والاحتفاء بما هو سائر في الأوساط الثقافية، فمن خاصية الخطاب السجالي التمرد، خاصة في ثقافتنا أو الوعي المجتمعي، ويحاول في الوقت ذاته فرض رؤى الذات المتساجلة وتصوراتها عن الوجود، فهو عدو الإبداع بسبب الموروث الذي يسيطر على أنه الأنموذج الذي ينبغي إتباعه والاحتفاء به. Abstract: The present study attempts to demonstrate that polemic discourse is an epistemological discourse that endeavours to contribute to and construct knowledge by presenting an epistemological alternative that enriches, nurtures knowledge and draws the principle of difference in opinion.It also defends the value of creativity that contradicts subordination, fossilisation and celebration of what is common in cultural circles. Then, polemic discourse is characterised by rebellion, especially in our culture or societal consciousness, while at the same time, it attempts to impose discernible self-perceptions and existence perceptions. It is the enemy of creativity because of the inheritance, which dominates as the model to be followed and appreciated. Key words: polemic discourse, polimecization, competence, Pilgrims , prejudice, knowledge
مقال
Keywords: الخطاب السجالي؛ المساجلة؛ الحجاج؛ الكفاءة؛ التحيز؛ المعرفة.